POLICY RESPONSE ON THE IMPACTS OF COVID 19 PANDEMIC ON UNEMPLOYMENT IN INDONESIA: Fadillah Putra, Anwar Sanusi, Muhyidin Muhyidin - Putra, Fadillah; Sanusi, Anwar; mahyidin, Mahyidin (LPPM STIA Nusantara Sakti, 2023)
The COVID-19 pandemic has seriously impacted the socioeconomic sector, including affecting the unemployment rate. This study evaluated the effectiveness of the government's social policies in responding to the economic crisis due to the pandemic and evaluated the traditions of citizenship and the welfare regime that existed in Indonesia during the crisis, especially to see the position of social policy during a crisis in Indonesia, which is rarely discussed. The data was collected using the questionnaire on unemployment in several big cities with a random sampling technique, and hypotheses were tested using the Structural equation modeling (SEM) method with LISREL 9.30 software to analyze the correlation between the impact of the COVID-19 pandemic on unemployment among individuals, communities, voluntary organizations, and the government. This study showed that citizenship traditions and welfare regimes are not necessarily associated with social policy performance; people tend to rely more on themselves and the surrounding community to overcome their financial problems than the government. This is closely related to the level of public trust in the government's ability to solve public problems. Furthermore, the performance of existing social policies is quite effective in the short term in overcoming the issue of unemployment.